Penyuluhan Penentuan Kualitas Air Tanah di Wilayah Perumahan Grand Sanur Griya Tama II Palangka Raya - Rokiy Alfanaar; Fatchiyatun Ni’mah; Marvin Horale Pasaribu; Tety Wahyuningsing Manurung; Mokhamat Ariefin; Efriyana Oksal (Yayasan Daarul Huda Kruengmane, 2023)
Water, the primary need of living things, is indispensable for humans. The use of water is a common thing in the community. One of the community environments that needs water is housing. Grand Sanur Griya Tama II Housing Estate, a housing estate in Palangka Raya City, is one of the places that utilize groundwater to meet clean water needs. In this service, counselling is carried out by determining groundwater quality based on physical and chemical parameters. The community service results show that the groundwater quality in the housing is in accordance with quality standards.